Pengaruh Program Kelas Unggulan Terhadap Prestasi Belajar Mata Pelajaran Akidah Akhlak Siswa Kelas VII B Di SMP Al Islam 1 Surakarta Tahun Ajaran 2022/2023 - Iftitah Amin Suryani; Nur Hidayah; Yunan Hidayat (Departement of Mathematics Education, 2023)
This study was to determine whether there was an influence of the superior class program on learning achievement in the Akidah Akhlak subject of Class VII B Junior High School Al Islam 1 Surakarta. Aqidah Akhlak lesson is a planned effort or effort in preparing students to know, understand, live and believe in Allah SWT and realize it in noble moral behavior in everyday life through guidance, teaching, training, using experience and habituation. The superior class is a class specifically designed for students who have more abilities, talents, skills, creativity, and intelligence than other students and then receive different teaching programs to increase these strengths in accordance with the developed curriculum. This type of research is quantitative research. The population in this study were 30 students of class VII B at SMP Al Islam 1 Surakarta. Retrieval of data in this study by questionnaire method. The collected data was analyzed using a questionnaire data collection technique. While the data analysis technique uses descriptive statistical techniques processed with the help of SPSS for windows. The results of this study indicate that 1) The Primary Class Program of SMP Al Islam 1 Surakarta is in the good category with an average of 43.3% entering in the 81-84 interval. 2) Learning Achievement at SMP Al Islam 1 Surakarta shows a good category with an average of 43.3% entering in the 88-91 interval. 3) There is a relationship between the Superior Class Program and the Akidah Akhlak Learning Achievement of Class VII B Students at SMP Al Islam 1 Surakarta, with a coefficient value of 0.80 which has a very strong correlation.